The biology of aquatic and wetland plants - Ervin, Gary N. (CRC Press, 2023)
Aquatic plants play a critically important role in maintaining ecosystem health. Despite this globally recognized importance, wetlands have faced and continue to face threats from the encroachment of human activities"-- Provided by publisher.